Peran Ankum Dalam Pemberian Sanksi Pelanggaran Disiplin Militer Dari Perspektif Keadilan dan Pembinaan Prajurit - Aldy Mirozul; Aprilian Nurahsan; M. Reza Saputra; Irwan Triadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The problem of disciplinary violations committed by soldiers is a sensitive issue considering the vital role of the military in maintaining the security and sovereignty of the country, therefore the role of Ankum as a direct superior who provides disciplinary law is very important for soldiers. Normative legal research or library legal research, with a statutory regulatory approach. The nature of this research is normative juridical because the researcher will analyze the role of Ankum in imposing disciplinary sanctions that adhere to the principles of justice and development. The results of the study The Role of Ankum in Imposing Sanctions for Military Disciplinary Violations from the Perspective of Justice and Development of Soldiers